Preliminary experience with lumbar facet distraction and fixation as treatment for lumbar spinal stenosis - Giovanni Grasso; Alessandro Landi (Journal of Craniovertebral Junction and Spine, 2017)
Objectives: To assess the properties of facet fixation with the Facet Wedge system in patients affected by lumbar spinal stenosis (LSS). Summary of Background Data: Implant of intra-articular spacers is an emerging technique for lumbar degenerative disease. Methods: This study included forty patients (Group 1) with symptomatic LSS in whom intra-articular spacers have been implanted along with microdecompression (MD) of the neural structures. Group 1 has been compared with a homogeneous group of patients with LSS treated with MD without intra-articular spacers implant (Group 2). Clinical findings have been observed preoperatively and 3, 6, 12 months postoperatively using dedicated questionnaires (Zurich Claudication Questionnaire, visual analog scale, and Oswestry disability index). Results: One year following surgical treatment, 87% of the patients presented with good improvement of symptoms and 97% referred satisfaction for surgery. Overall, patients of Group 1 presented with significantly better clinical outcome when compared with the control group (P < 0.01). Conclusions: Intra-articular spacers showed significant and clinically meaningful improvements in pain and disability for up to 1 year. These findings need further studies and a longer follow-up.